MUC503 : Teknologi audio digital untuk komposer / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to Digital Audio Workstation (DAW) tools and techniques in music composition and audio design. Students are expected to describe the application of digital audio editing and mixing techniques in their work production by using appropriate DAW. In addition, students are required to demonstrate autonomous learning in digital multi-track recordings using humanization techniques.